2017
DOI: 10.1177/0363546516688636
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Hip Impingement Surgery: Does Generalized Joint Hypermobility Matter?

Abstract: FAI surgery yielded favorable outcomes at short- to midterm follow-up. JH as assessed by the Beighton score was not consistently associated with subjective and objective results. Joint degeneration was the most important risk factor for conversion to THR. Although statistical significance was not reached, female patients with no joint degeneration, only mild FAI deformity, and higher Oxford scores at the time of surgery seemed to be at increased risk for subjective dissatisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Weber et al found that capsular plication in athletes may actually impair RTS by limiting the external rotation necessary for complex sports [43]. On the contrary, studies have also shown no significant relationship between Beightons scores and functional outcomes following hip arthroscopy [44,45]. It seems that patients with greater internal or external rotation have increased joint instability that may preclude them from returning to their sport.…”
Section: Discussionmentioning
confidence: 99%
“…Weber et al found that capsular plication in athletes may actually impair RTS by limiting the external rotation necessary for complex sports [43]. On the contrary, studies have also shown no significant relationship between Beightons scores and functional outcomes following hip arthroscopy [44,45]. It seems that patients with greater internal or external rotation have increased joint instability that may preclude them from returning to their sport.…”
Section: Discussionmentioning
confidence: 99%
“…(40) On the contrary, studies have also shown no significant relationship between Beightons scores and functional outcomes following hip arthroscopy. (41,42) It seems that patients with greater internal or external rotation have increased joint instability that may preclude them from returning to sport.…”
Section: Discussionmentioning
confidence: 99%
“…The Breighton scale is commonly used to quantify the degree of soft tissue laxity in the clinical setting. 27 Patients with hypermobility often carry the diagnosis of Ehlers-Danlos syndrome or other conditions with increased soft tissue laxity and can have significant hip-related symptoms. 28 Anterior impingement is reproduced with the hip in maximal flexion, internal rotation, and adduction.…”
Section: Physical Examinationmentioning
confidence: 99%